Narrative Analysis of Marketing Communication Y2K Music School and Studio on Social Media - Tuti Widiastuti; Poppy Ruliana (Sekolah Tinggi Ilmu Komunikasi Inter Studi, 2017)
This research was conducted to find out how the branding activity done by Y2K Music School and Studio through social media account Instagram @ y2kstudio. This research would like to examine more deeply related to marketing activity such as what applied Y2K Music School and Studio in building brand Y2K Music School and Studio as a music school through its official Instagram. There is also a method used in this research is a method of narrative analysis which is a method in the field of qualitative research. The data were collected using literature study on textbooks, online data tracking, and in-depth interviews on key informants related to the study. The results of this study states that the form of branding activities conducted by Y2K Music School and Studio through social media accounts Instagram @ y2kstudio is a marketing communication in the form of delivering information with positive ambiance related Y2K Music School and Studio and also in the form of information delivery activities related promotions which is currently running at Y2K Music School and Studio.